The Effect of Training and Competency on the Performance of Employees with Work Facilities as Intervening Variables at the Manpower, Cooperatives, Small and Medium Enterprises Office of Serdang Bedagai Regency - Yusvarilda Syafiah; Husni Muharram Ritonga; Elfitra Desy Surya (CV. Doki Course and Training, 2026)
This study aims to examine the influence of training and competence on employee performance, with work facilities as intervening variables at the Department of Manpower, Cooperatives, Small and Medium Enterprises of Serdang Bedagai Regency. This study uses an associative quantitative approach with a census method involving 35 employees as respondents. The data was analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS software. The results showed that competence had a positive and significant effect on employee performance (β = 0.866; t = 5.687; p < 0.05), so the hypothesis was accepted. In contrast, training did not have a significant direct effect on employee performance (β = 0.494; t = 1.512; p > 0.05), so the hypothesis was rejected. Furthermore, training had a positive and significant effect on work facilities (β = 0.969; t = 13.818; p < 0.05), which showed that the hypothesis was accepted, while competence had no significant effect on the work facilities (β = 0.014; t = 0.182; p > 0.05), so the hypothesis was rejected. The results of the study also showed that work facilities did not have a significant effect on employee performance (β = −0.451; t = 1.429; p > 0.05). The mediation analysis confirmed that work facilities did not mediate the relationship between employee training and performance (β = −0.437; t = 1.339; p > 0.05) or between employee competence and performance (β = −0.006; t = 0.163; p > 0.05). These findings show that competence is the most dominant factor in directly influencing employee performance, while training and work facilities have no significant direct or mediating influence. It is recommended that organizations prioritize ongoing competency development and design training programs that are more suited to job demands to improve employee performance.